Clinical utility of R-OPS score in the preoperative diagnosis of ovarian cancer: a prospective cohort study - Vo, Hoang Lam; Nguyen, Hoang; Nguyen, Xuan Anh Thu; Nguyen, Khoa Bao; Tran, Trong Duy; Truong, Quang Vinh (Tạp chí Y Dược Huế, 2025)
Objective: This study aimed to validate the diagnostic utility of the Rajavithi-Ovarian Cancer Predictive Score (R-OPS) in preoperative ovarian cancer diagnosis and compare its efficacy with that of the Risk of Ovarian Malignancy Algorithm (ROMA). Methods: A prospective cohort study was conducted at two hospitals in Vietnam from January 2024 to January 2025, involving 215 patients with adnexal masses (69 malignant, 146 benign) who underwent surgery. R-OPS was calculated using menopausal status, ultrasound findings, and serum cancer antigen 125 (CA125) and human epididymal protein 4 (HE4) levels. Results: R-OPS achieved an AUC of 91.4% (95% CI: 87.0 - 95.7%). At a cut-off of > 330, it displayed a specificity of 95.2% and a sensitivity of 71.0%, with positive and negative predictive values of 86.0% and 87.3%. R-OPS outperformed ROMA by 5.9% in AUC (P<0.001). Conclusion: R-OPS is an effective tool for preoperative differentiation between benign and malignant ovarian masses, demonstrating superior performance compared to ROMA.